Primary colorectal lymphoma – A single centre experience. Issue 3 (June 2015) - Tevlin, R.; Larkin, J.O.; Hyland, J.M.P.; O'Connell, P.R.; Winter, D.C.
Abstract: Purpose: The incidence of primary colorectal lymphoma (PCL) is rare (0.2–0.6% of large bowel malignancy). Up to one third of Non-Hodgkin's lymphoma will present with extra-nodal manifestations only. Extra-nodal lymphomas arise from tissues other than the lymph nodes and even from sites, which contain no lymphoid tissue. The incidence of Non-Hodgkin's lymphoma has increased over the past fifty years. The objective of this study was to examine our experience of PCL. Methods: A prospectively-compiled database (1988–2012) of patients with colorectal cancer was retrospectively examined for cases of colorectal lymphoma. A retrospective chart review identified cases of PCL based on Dawson's criteria. Clinical information was obtained from case notes. Results: Eleven patients (0.3% of 4219 patients) were identified (6 male, 5 female). The median age at diagnosis was 63 years. Mode of presentation varied; abdominal pain, a palpable mass and per rectal bleeding being the most frequent. The caecum was the most frequently involved site (5/11). Nine patients underwent surgical management, one had chemotherapy alone and one had radiotherapy alone. All cases were non-Hodgkin's lymphoma, with diffuse large B-cell lymphoma in majority. The median event-free survival of those treated with surgery and post-operative chemotherapy was 10 months (range 5–120 months). Conclusion: Primary colorectal lymphoma is rare. Management is multidisciplinary and dependent on the subtype of lymphoma. Due to the rarity of diagnosis, there is a paucity of randomised control trials. Most information published is based on individual case reports and there is, thus, no clear treatment algorithm for these cases.